Heavy minerals as a tool to reconstruct river activity during the Weichselian glaciation (Toruń Basin, Poland) - Weckwerth, Piotr; Chabowski, Marek (Geologos, 2013)
The heavy-mineral composition of the Weichselian fluvial successions deposited by an ephemeral meandering river and by a sand-bed braided river in the Toruń Basin (central Poland) was analysed. On the basis of a lithofacies analysis, in combination with the composition of the heavy-mineral assemblages, the fluvial processes and river-channel morphology were reconstructed. This allows determining the provenance of the fluvial deposits and the rivers’ discharge regimes. A model is proposed which can explain the changes in the amount of individual minerals in the fluvial sediments of different ages under the conditions of the oscillating Scandinavian ice sheet. The model assumes that, during the ice-sheet advances, the proglacial streams supplied large amounts of heavy minerals that were less resistant to mechanical abrasion. During the main phase of the ice-sheet retreat, the distance between the ice sheet and the Toruń Basin increased, and the amount of non-resistant minerals diminished as a result of sediment reworking in proglacial rivers. Due to the unique location of the Toruń Basin at the front of the Scandinavian ice sheet during the Weichselian glaciation, the heavy-mineral assemblages in the fluvial deposits form a valuable tool for the recognition of the ice-sheet extent.